Prediksi Kedatangan Wisatawan Pada Pariwisata Kota Batam Dengan Menggunakan Teknik Knowledge Data Discovery - Andi Supriadi Chan (JURNAL ILMIAH INFORMATIKA, 2018)
This geographical condition is an important component in the development of tourism in Indonesia. Batam or "Great Batam" is one of the three main entrances of tourism in Indonesia, with the third largest tourist arrivals after Bali and Jakarta. the number of foreign tourists who enter the city of batam in 2014 as many as 1.435 million people with the dominance of tourists from singapore, not to mention the number of local tourists who enter the city of batam a number of 1.609 million in 2014With the high number of tourist arrivals to batam city. So it is necessary strategies and policies undertaken by the local government in the management and construction of facilities and infrastructure that can support the development and advancement of tourism in the city batam, with that it is necessary to calculate the policy on the development of facilities and infrastructure required by the tourists visit to batam city. Knowledge management one of them by using algorithm method C4.5 can be used by government, Government purpose applying Knowledge management is to keep the knowledge do not just disappear and can be sharing with other employee in other government to support decision making in constructing facilities and infrastructure needed for the number of tourist arrivals to the city batam increasing